ENHANCING STUDENTS’ LEARNING INTEREST THROUGH GAMESHOW-BASED QUIZ MEDIA IN QUR’ANIC LEARNING CENTERS - Abdul Latif; Adhi Setiyawan; Muhammad Zaki Ridho Djakfar; Dani Alamsyah; Evi Sulfaningsih (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study aimed to compare students’ learning interest before and after the use of Wordwall (Gameshow Quiz) and to examine its effectiveness in enhancing learning interest in non-formal Qur’anic education. A quantitative approach was employed using a pre-experimental design with a one-group pretest–posttest model. Data were analyzed using a paired sample t-test and n-gain analysis. The results revealed a statistically significant difference between pretest and posttest scores, with a p-value of 0.000 < 0.05, indicating an increase in students’ learning interest after the intervention. The average n-gain score was 0.43, which falls within the moderate effectiveness category. These findings suggested that interactive digital media such as Wordwall can meaningfully enhance students’ learning interest in Qur’anic instruction. The study implied that integrating technology-based learning media in QLCs might serve as an effective pedagogical strategy to improve student engagement in non-formal Islamic education settings.